Essential Oil and Bioactivity of the Ziziphora canescens Benth. Growing Wild in Lebanon - Jaoudeh, Chantal Abou; Baydoun, Safa; Arnold, Nelly (Pharmacognosy Communications)
Introduction: Ziziphora canescens Benth. (Lamiaceae) is a medicinal plant widespread species in Mediterranean countries. This study was designed to evaluate the chemical composition and in vitro antimicrobial activities of this species growing wild in Lebanon. Material and Methods: The essential oil of the dry aerial flowering parts of Z. canescens from the Lebanese side of Mount Hermon (1843 m altitude above sea level) was obtained by hydrodistillation. The GC-MS analysis of the obtained essential oil was performed. The antimicrobial activity of the oil was tested against six certified bacteria and two certified fungi using disc-diffusion method and determination of the minimal inhibitory concentration (MIC) by agar dilution method. Results and Discussion: The yield of essential oil was 0.6ml/100g dry weight. GC -MS analysis revealed twenty eight components representing 93.0% of the total essential oil. Oxygenated monoterpenes (80.6%) were the predominant fraction of the essential oil with pulegone (39.2%), eucarvone (12.6%), D-menthone (10.3%), 3-cyclohexen-1-one, 2-isopropyl5-methyl- (9.1%). The oil exhibited a broad-spectrum of antimicrobial activity against the tested pathogenic microorganisms. The yeast Candida albicans and Salmonella enteritidis were the most susceptible with growth inhibition zones of 40.5 ± 0.7 mm and 29.0 ± 0.7 mm, respectively, and MIC values of 5µg/ml. These values were similar to those of pulegone and each the antibiotics Nystatine and Amikacine, respectively whilst, the fungus Trichophyton mentagrophytes was the most resistant. Conclusion: The results of this study support the notion that the essential oil of Z. canescens Benth. may be important as a pharmaceutical and food preservative.
Keywords: Antimicrobial activities; Chemical composition of essential oil; Eurcarvone; Pulegone; Ziziphora canescens Benth